Lower-limb function among former elite male athletes - Kettunen, J. A.; Kujala, U. M.; Kaprio, J.; Koskenvuo, M.; Sarna, S. (The American Journal of Sports Medicine, 2001)
To determine the relationship between previous lower-limb loading and current self-reported hip and knee disability, we sent a questionnaire to 1321 former elite male athletes who had represented Finland between 1920 and 1965 in international competitions and to 814 control subjects who had been classified as healthy at the age of 20. After adjustment for age, body mass index, and occupational group, the odds ratios of hip disability in the athletes compared with control subjects were 0.35 in endurance athletes (95% confidence interval, 0.14 to 0.85, P = 0.02), 0.56 in team sport athletes (0.28 to 1.10, P = 0.09), 0.30 in track and field athletes (0.12 to 0.73, P < 0.01), 0.84 in power sport athletes (0.51 to 1.39, P = 0.49), 0.30 in shooters (0.07 to 1.32, P = 0.11), and 0.54 (0.36 to 0.82, P < 0.01) in all athletes combined. Compared with control subjects, only team sport athletes had a higher risk of knee disability (odds ratio, 1.76; 95% confidence interval, 1.03 to 3.02; P = 0.04). Even though athletes have been reported to be at an increased risk for lower-limb osteoarthritis, our data show that former elite male endurance and track and field athletes and all athletes combined reported less hip disability than the control subjects. The effect of vigorous athletic activity on the function of knee joints is more controversial, because sports that involve a high risk of knee injury are likely to lead to pain, disability, and osteoarthritis.